Economic evaluation of preventive cognitive therapy versus care as usual in cognitive behavioral therapy responders - de Jonge, Margo; Blankers, Matthijs; Bockting, Claudi L. H.; van Dijk, Maarten K.; Kikkert, Martijn J.; Dekker, Jack J. M. (Frontiers in Psychiatry, 2024)
Background: The highly recurrent nature of Major Depressive Disorder is a major contributor to disability and health care costs. Several studies indicate that recurrence may be prevented with Preventive Cognitive Therapy (PCT). This study is the first to perform an economic evaluation of PCT in comparison with care as usual for recurrently depressed patients who experienced two or more depressive episodes and remitted after receiving Cognitive Behavioural Therapy. Methods: An economic evaluation from the societal perspective was performed alongside a randomized trial (N=214). Health-related quality of life (QALYs), depression-free days, health care utilization, and productivity losses were measured between randomization and 15 months follow-up. The costs were indexed to the reference year 2014. Results: QALY gains did not differ significantly between the groups (P = .69). Depression-free days were higher after PCT (P = .02). Societal costs of PCT were 10,417 euro and for care as usual 9,545 euro per person. We found a 47% likelihood that PCT led to additional QALYs at higher costs, and there was a 26% likelihood that PCT led to fewer QALYs at higher costs. When depression-free days was used as an outcome, we found PCT had a 72% likelihood of leading to more depression-free days at higher costs than care as usual and a 27% likelihood of leading to more depression-free days at lower societal costs. Limitations: The 15-month follow-up might be too short to draw long-term conclusions about the cost-effectiveness of the PCT. The data collected for this study is part of an RCT to examine the effectiveness of adding PCT to care as usual. Therefore, the study was powered primarily to detect an effect in time to relapse/recurrences. Conclusions: The economic evaluation is slightly in favour of the PCT condition when depressionfree days is used as an outcome. PCT is not cost-effective given the high costs per additional QALYs from the societal perspective when QALYs are the effect measure. Trial registration: Netherlands Trial Register (NTR) www.trialregister.nl: 2599.